Maintenance scheduling of a protection system subject to imperfect inspection and replacement - Berrade, M.D.; Cavalcante, Cristiano A.V.; Scarf, Philip A. (European journal of operational research, 2012)
► The paper models quality of maintenance interventions. ► It considers replacement and inspection of a non-repairable protection system. ► Substandard replacements and false positive inspections combine to reduce system availability. ► We quantify this reduction and the associated cost. ► A packaging machine case study illustrates our ideas. An inspection and replacement policy for a protection system is described in which the inspection process is subject to error, and false positives (false alarms) and false negatives are possible. We develop two models: one in which a false positive implies renewal of the protection system; the other not. These models are motivated by inspection of a protection system on the production line of a beverage manufacturer. False negatives reduce the efficiency of inspection. Another notion of imperfect maintenance is also modelled: that of poor installation of a component at replacement. These different aspects of maintenance quality interact: false alarms can, in a worst case scenario, lead to the systematic and unnecessary replacement of good components by poor components, thus reducing the availability of the system. The models also allow situations in which maintenance quality differs between alternative maintainers to be investigated.